On a possibility to introduce a private insurance of expenses created in the procedure of bio-medically assisted fertilization (IVF) - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
According to the most recently available data, between  7 and 9 percent of couples who wish to have children suffer from various kinds of  infertility. Through application of different methods and procedures of modern medicine the problem of infertility can be solved in about 85 to 90 percent of cases. This is primarily due to development of various procedures bio-medically assisted fertilization (hereon after: IVF). However, expenses of those procedures are still exceptionally high. Furthermore, it should be noted that the successfulness of the IVF in one cycle amounts to 25 to 30 percent. This is the reason why there is often a need to go through 3 to 4 cycles in order to achieve desired result. Couples who enter the procedure of IVF attempt in several ways to overcome or at least reduce financial difficulties connected with it. On method of overcoming financial difficulties, still unavailable in Serbia, is private insurance that would cover the expenses created in connection with the IVF. Unlike insurance laws of developed countries (i.e. Germany, United States etc.), insurance companies in Serbia do not include this type of insurance in their offer of private health insurance. Moreover, typical policies of private health insurance explicitly exclude expenses incurred through treatment of infertility and application of the IVF procedure. This paper deals with a possibility of introduction of this type of insurance to the practice of Serbian insurance companies, as well as conditions which could be set for realization of claims based on it.